Curzerene suppresses hepatocellular carcinoma progression through the PI3K/AKT/MTOR pathway - Yihui Luo; Zhenchang Wang; Jun'e Jiang; Shanshan Wu; Yang Zhai (Permanyer, 2024)
Background: Hepatocellular carcinoma (HCC) is one of the most aggressive cancers worldwide. Curzerene is a sesquiterpene and component of Curcuma rhizomes and has anti-tumor and anti-inflammatory properties. Objective: The study aimed to investigate the effects of curzerene on the malignant phenotypes and tumor growth in HCC. Methods: Various concentrations of curzerene were used to treat human HCC cells (Huh7 and HCCLM3). Cell viability, apoptosis, cell cycle, invasion, and migration were detected by 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, flow cytometry, Transwell, and wound healing assays. Cell cycle-, apoptosis-, and signaling pathway-related proteins were analyzed by Western blot analysis. A mouse xenograft model was established to analyze the anti-tumor effects of curzerene in vivo. Results: Curzerene repressed the proliferation, invasion, and migration of Huh7 and HCCLM3 cells. Curzerene also induced G2/M cycle arrest and cell apoptosis. Curzerene downregulated the CDK1, cyclin B1, PCNA, Bcl-2, matrix metallopeptidases (MMP)2, and MMP9 protein expression and upregulated the Bax, cleaved caspase3, and cleaved poly ADPribose polymerase protein expression in HCC cells. Curzerene restrained the phosphorylation of PI3K, AKT, and the Mammalian target of rapamycin (mTOR) in Huh7 and HCCLM3 cells. The in vivo data revealed that curzerene inhibited HCC tumor growth and decreased the expression of phosphorylated mTOR in xenograft mouse models. Conclusion: Curzerene inhibited cell malignancy in vitro and tumor growth in vivo in HCC, suggesting that curzerene may be a candidate agent for anti-HCC therapy.